La quête identitaire dans l’œuvre romanesque d’Ananda Devi - Szkonter-Bochniak, Anna (Romanica Silesiana)
This article examines three novels by Ananda Devi, a well‑known francophone novelist from Mauritius, the author of many novels, short stories and poetry books. In her novels, theauthor portrays the lives of women, the roles and norms that have been imposed on them, as well as their place in the conservative and patriarchal society in Mauritius and in India. The protagonists of Pagli, Le Voile de Draupadi and Indian tango, whilst searching for their identity, rebel against the society, their families and religion which marginalise them and deny their right to make decisions about their own lives. The protagonists of Devi’s novels by objecting to such a lifestyle, by violating the social norms and breaching bans, discover their identity. Pagli symbolically rediscovers her true name, Anjali freedom and Subhadra her body/sexuality. Key words: Ananda Devi, francophone novel, woman, identity, freedom, violation of social, religious and moral norms